From complex social interventions to interventions in complex social systems: Future directions and unresolved questions for intervention development and evaluation. (January 2019) - Moore, Graham F.; Evans, Rhiannon E.; Hawkins, Jemma; Littlecott, Hannah; Melendez-Torres, G.J.; Bonell, Chris; Murphy, Simon
Complex systems approaches to social intervention research are increasingly advocated. However, there have been few attempts to consider how models of intervention science, such as the UK's Medical Research Council complex interventions framework, might be reframed through a complex systems lens. This article identifies some key areas in which this framework might be reconceptualized, and a number of priority areas where further development is needed if alignment with a systems perspective is to be achieved. We argue that a complex systems perspective broadens the parameters of 'relevant' evidence and theory for intervention development, before discussing challenges in defining feasibility in dynamic terms. We argue that whole systems evaluations may be neither attainable, nor necessary; acknowledgment of complexity does not mean that evaluations must be complex, or investigate all facets of complexity. However, a systems lens may add value to evaluation design through guiding identification of key uncertainties, and informing decisions such as timings of follow-up assessments.